Field demonstration of continuous monitoring of a steel railway bridge - Deepthi, T.M.; Saravanan, U.; Prasad, A. Meher (Journal of Structural Engineering, 2024)
Many railway bridges in India are aged requiring an analysis on their current health. Appropriate instrumentation is necessary to determine the health of the bridges. This paper explains the instrumentation philosophy followed and its implementation in the field for continuous monitoring of a railway bridge. The bridge considered for this study is a single span steel plate girder bridge. Using a wired data acquisition system the bridge was monitored for 125 days. Also, an economical wireless data acquisition system developed in-house was validated using this wired data acquisition system. Finally, the collected strain time histories are summarized in the form of count versus strain range, as determined from the rainflow count algorithm. Thus, a viable methodology for continuous monitoring of railway bridges is demonstrated which may be used to assess the health of the bridge and arrive at rational design loads for railway bridges.